Social tillfredsställelse i bostadsområden : Analys av stadskvaliteter och resursbehov applicerat på närområdet till Kronan i Luleå - Nyström, Sara (2014)
A city consists of a number of factors that can be described in terms of its character and content, also called urban qualities. For a society to function and for people who want to settle there, the site must contribute to satisfy citizens' functional needs as well as social needs.An interaction of factors requires in the city to be able to satisfy citizens' satisfaction and needs at the same time. The factors or characteristics that arise in a residential area are called urban qualities and have been developed and analyzed in a study of literature based on previous studies conducted in the subject with a focus on socially sustainable cities. The urban qualities can be summarized and defined as: safety and security, community, physical and aesthetic environment, commercial service, green areas, water areas, communications and the location in the city.Urban qualities appear to be of a more or less value to the residential areas depending on location, type of population and situation. City's residential areas are unique in themselves, they all differ and the people who live there can have contrary opinions unlike another area,therefore the grades of the urban qualities should be tested individually on each site. With the basis in the study of literature the development of the significant urban qualities designed an empirical study in the thesis to be applied to the district Kronan and the two adjoiningdistricts Lulsundet and Skurholmen in Luleå. The purpose of the analysis is to add value to Kronan, both as a residential area and as a part of Luleå. The residents at Kronan should feel satisfied with their immediate environment as well as attract visitors because of its rangeof services and other resources. Along with the housing establishment different commercial service operations will be introduced, depending on the needs that will be developed throughout this study. The objective of this study is to find a good basis for Kronan to become a functional residential area with a mixed composition of service, ...